Pricing Practices on Digital Platforms from the Perspective of Islamic Business Ethics: A Study of Marketplace Operators in Indonesia - Fadhila Sukur Indra; Miftahul Huda (Nuban Jagadhita Centre, 2026)
Objective: This study aims to analyze the pricing mechanisms on digital platforms, identify the factors influencing price volatility, and examine these mechanisms from the perspective of Islamic business ethics. Method: This study employs a qualitative field case study approach in Indonesia. Primary data was collected through in-depth interviews with marketplace business operators selected via purposive sampling. Data analysis applied the interactive model proposed by Miles, Huberman, and Saldaña. Results: Research findings indicate that pricing on digital platforms is dynamic (dynamic pricing) and highly responsive to platform structure, moving beyond the conventional cost-plus pricing method. Prices are determined through real-time interactions between internal cost calculations, competitive strategies among stores, platform algorithms, promotional momentum (such as flash sales or date-matching promotions), and consumer perceptions of value. This strategy is crucial for sellers to maintain product visibility and competitiveness. However, this pricing structure is often not fully understood by buyers, leading to information asymmetry. Implications: Ethically, price flexibility aligns with the principle of al-’adl and free-market mechanisms. However, this paper emphasizes the need for transparency (bayān), mutual consent (tarāḍin), and trustworthiness; thus, psychological manipulation such as raising prices before applying a discount is deemed ethically flawed. Accountable platform governance and the strengthening of consumer digital literacy are required. Novelty: This study lies in a shift in the focus of academic analysis from a previous tendency to treat price solely as a static economic variable influencing purchasing decisions to an analysis of socio-technological processes. This study examines how digital prices are constructed as the result of complex negotiations mediated by socio-economic technologies (algorithms and platform interface design) and are empirically evaluated using the substantive principles of Islamic mua'malah ethics.